Pengaruh Harga, Kelengkapan Produk, Dan DisplayProduk Terhadap Pembelian Ulang(Studi Kasus Pelanggan Konsumen Di Swalayan Mitra Karanganyar) - , Ariyanti; , Imronudin, S.E,.,M.Si., Ph.D (2017)
This study aimed to test how pricemaker, completeness of product and placement of purchase at Supermarket Mitra Karanganyar. The method of collecting the product (product display) on the purchasing decisions of consumers in supermarkets Partners Karanganyar. The population is all consumers who did sample using convenience sampling. The research sample of 100 respondents who had made purchases in Supermarket Mitra Karanganyar. Based on the result is that the price variables significantly influence purchasing decisions. Variable range of products significantly influence purchasing decisions and variable placement (display product) significant influence on purchasing decisions. It can be concluded that the determinants of price, Fittings Products and Product Placement (display product) affects consumers in catering Karanganyar Partners to buy or shop again, especially in terms of competitive pricing by the management of self-service.